Why private sector investment is important for alpaca and vicuña fibre trade sustainability: A case study from Tolconi Arequipa in the southern Andes in Peru - Michaud, E. (2025)
A presentation contributing to the panel on "Sustainable Livestock Systems. What Role for Private Sector?" organized by ILRI and partners on the project STELARR (Sustainable Large-Scale Investments in Rangeland Restoration) at UNCCD CRIC 23, Panama City, December 1st, 2025.